Limited Spin: When the Public Punishes Leaders Who Lie about Military Action. (February 2021) - Maxey, Sarah
Presidents have significant incentives to mislead the public about the use of force. Under what conditions are members of the public willing to hold presidents accountable for what they say about military action? This article examines both spin and deceit at the micro-level to clarify when individuals are most likely to punish presidents for misinformation. Three survey experiments demonstrate that presidents incur political costs for misinformation, even when operations succeed. Introducing partisanship into the analysis then reveals that not all individuals are equally likely to punish all presidents—Republican leaders primarily concerned with their base have the most leeway to mislead. The findings highlight the dynamic nature of democratic accountability and domestic constraints on military force. Rather than a static institutional feature, the strength of accountability can vary across presidents and electoral coalitions. Additionally, the results show political costs are not limited to large-scale deception—even spin generates backlash.